ISLAMIC MICRO FINANCE DEVELOPMENT: CHALLENGES AND INITIATIVES - Bin Amin, Md. Fouad (International Journal of Economics, Management and Accounting, 2013)
Edited by Mohammed Obaidullah, and Tariqullah Khan